2002
DOI: 10.1007/s00056-002-0118-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Fixed Functional Appliance for Treatment of Skeletal Class II Malocclusion

Abstract: Developed under interdisciplinary cooperation, the Functional Mandibular Advancer (FMA) is a new, rigid and fixed appliance for sagittal correction of the intermaxillary jaw relationship in adolescents and young adults. The appliance is non-dependent on patient compliance and is aimed at providing an alternative to the Herbst and MARA appliances. A number of designs, all based on the mechanical principle of the inclined plane combined with guide pins and allowing reactivation, were developed. The version of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 50 publications
(29 reference statements)
0
14
0
4
Order By: Relevance
“…The Functional Mandibular Advancer (FMA; Forestadent, Pforzheim, Germany), 17 introduced in 2002 (later than the Mandibular Advancement Repositioning Appliance [MARA]), 18 is a fairly new, rigid, fixed functional appliance. In contrast to the MARA, which had the guiding elbows fixed to the maxillary first molars at right angles to the occlusal plane, 19 the FMA has an inclined plane (at 608 to horizontal) which is one of the fundamental concepts of functional jaw orthopedics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Functional Mandibular Advancer (FMA; Forestadent, Pforzheim, Germany), 17 introduced in 2002 (later than the Mandibular Advancement Repositioning Appliance [MARA]), 18 is a fairly new, rigid, fixed functional appliance. In contrast to the MARA, which had the guiding elbows fixed to the maxillary first molars at right angles to the occlusal plane, 19 the FMA has an inclined plane (at 608 to horizontal) which is one of the fundamental concepts of functional jaw orthopedics.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the MARA, which had the guiding elbows fixed to the maxillary first molars at right angles to the occlusal plane, 19 the FMA has an inclined plane (at 608 to horizontal) which is one of the fundamental concepts of functional jaw orthopedics. 17 A stepwise advancement protocol can easily be performed by moving the protrusive guide pins to a more anterior position via the mounting plate with threaded inserts. 5,17 No study has been undertaken to determine whether there is any difference between the two modes of mandibular advancement during FMA treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbst-Apparatur (Dentaurum, Ispringen, Deutschland), Jasper Jumper™ (American Orthodontics, Sheboygan, WI, USA), justierbarer Bite-Korrektor (The Adjustable Bite Corrector™, Ortho Plus Inc., Santa Rosa, CA, USA), Eureka-Feder (Eureka Spring Co., San Luis Obispo, CA, USA), und intramaxilläre Apparaturen, z.B. Pendulum, Distal Jet (American Orthodontics, Sheboygan, WI, USA), abstoßende Magneten, Jones Jig™ (American Orthodontics, Sheboygan, WI, USA), Molarendistalisationsbogen [23,[27][28][29][30]33]. Diese Apparaturen sind weniger von der Mitarbeit der Patienten abhängig und führen zu schnelleren Resultaten mit optimaleren Kräften.…”
Section: Introductionunclassified
“…[7][8][9][10] The original design and all its modifications, however, incorporate an inclined plane in the mandible and guide bars in the maxilla as the mechanism of action. 11 Numerous studies 3,7,8,[12][13][14][15] have verified the effectiveness of the double-plate system in treating Class II/ 1 malocclusions. A recent randomized, controlled trial carried out by Martina et al 15 concluded that BJA effectively corrects Class II malocclusions and produces a significant increase in mandibular length, reduction in dental overjet, and improvement in molar relationship.…”
Section: Introductionmentioning
confidence: 99%